Real-Time Data Capturing for Reservoir Spillway Gate Operation Via Mobile Device - Faisal, Zulhumadi (2006)
The operation of reservoir spillway gates at Timah Tasoh dam is based on a decision making process that relies on experience and an accurate data capturing method. Gate operation reliability is of utmost importance in order to deal with highly critical events such as excessive water flow or spill over. However, the current data capturing method is error prone and subjected to massive time delays. In times of emergency, such as flooding or critically high water levels, such deficiencies could lead to disastrous results. With the rapid advancement in the fields of Decision Support Systems (DSSs) and mobile computing, many tools can be used to support the already existing system. Furthermore, there are a number of Java compliant phones that are readily available and, chances are, these devices are already owned by these individuals. This project had adopted the Design Research (DR) methodology that involved a Real-Time Data Capture (RTDC) component coupled with a Temporal Data Mining (TDM) engine, packaged in a mobile application. Java Micro Edition (JME) formerly known as J2ME was used as the programming language, and a mobile phone emulator was used to demonstrate the application. The results of this project had revealed that for a mobile application to be successfully implemented, factors such as the Graphical User Interface (GUI), persistent record maintenance, and the Connected Limited Device Configuration (CLDC) and Mobile Information Device Profile (MIDP) platform versions must be considered and evaluated. There were also restrictions which have to be overcome in order to produce a fully fledged decision support system in a Java compliant mobile device,like the mobile phone.